Al-Lam Li-Ta’lil and Lam al-Amr on I’rab of Present Tense and its Relationship to Arabic Language Proficiency/Al-Lam li al -Ta‘lili wa Lam al-Amri fi I‘rabi al-Fi‘li al-Muḍari’i wa ‘Alaqatuhuma bi Kafaati al-Lughah al-‘Arabiyyah - Holilulloh, Andi; Nisai, Lu’luun; Ahmed, Essam Mustafa (Universitas Islam Negeri Raden Intan Lampung, 2025)
The differences in the reading of I'rab Fi'il Mudhari occur in several verses of Al-Qur'an. The reading method used by Imam Hafsh ibn Ashim is different from some other readers. This research examines both the difference in the syntax of the present tense in the frequent Qur’anic readings that related to meanings, and the difference in the structure of the present tense in the frequent Qur’anic readings with an explanation of the impact of this difference in the noble verse and contribute to building the linguistic ability of the students. Because of the difference in the way of reading Fi'il mudhari that occurs with the presence of Lam ta'lil and Lam al-Amr in the Al-Qur'an which are various differences. Object of this research is several verses of the Holy Qur'an which are subjected to Lam at-ta'lil and Lam al-Amr by using qualitative methods that focus on data analysis. This can provide additional ways in improving Arabic language proficiency. The main reference sources in this research are Al-Qur'an and the Book of Nahwu Al-Bayan fi Gharibi I'rab al-Qur'an. It is not a condition for the present tense to be in the accusative case of La ta’lil. The present tense verb with Lam li at-ta’lil was read with the kasra of the lam and the accusative, and with the sukun of the lam and the jazm so that research can contribute to improving Arabic language proficiency in terms of learning.